Removal of Methylene Blue from Aqueous Solution with Silica Gel Extracted from Coal Fly Ash - Melvi Muharmi (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2026)
The textile industry has the potential to cause water pollution due to dye waste such as methylene blue (MB). Many methods have been developed to overcome the challenges of dye removal, one of which is the adsorption method. This study introduces silica gel (SiG) as an effective material for MB dye wastewater treatment. The silica source was extrated from coal fly ash (FAC) which has a relatively high silica content, making it a potential silika source for silica gel synthesis. The silica gel formed was characterized using FTIR and SEM. The characterization results showed the presence of silanol and siloxane groups in the synthesized SiG. the morphology of SiG was spherical, non-agglomerated with fairly uniform particle size. This study also investigated the effect of pH, contact time, and adsorbent dosage on the MB dye adsorption process. The optimum conditions were obtained at pH 11, contact time 75 minutes and adsorbant dosage 0,1 gram with an adsorption efficiency of 89,49%. Therefore, this synthesized silica is promising for the efficient removal of MB dye from aqueous solutions and offers practical applications in wastewater treatment.